Assessment The Effects Of Climate Factors On Marshes Of Southern Iraq By UsingSatellite Images - AL- Saadi, Kasem; Naqi, Noor (Iraqi Journal of Science, 2024)
Remote sensing techniques have been used to measure the changes of IraqiMarshland’s area as well as the changes in the spectral reflectivity of types coveredin the Marshland (water, soil and plants). This study comprises the main threeMarshes in southern Iraq (Huwyizamarsh, Central Marshes and Hammar marsh).Satellite images of the satellite Terra-Modis on 15/1/2009, 20/4/2009, 21/8/2009 and7/11/2009 have been selected in order to study the seasonal changes on the marshestook place during 2009. Result of supervised classification indicated presence on sixland cover classes in marshes.The study shows that the dry soil reflectivity wasn’tobviously influenced by the climatic factors and that both temperature andevaporation influence directly on the other classes reflectivity. The rainfall influencereversely on the reflectivity of the dark soil, dense and spread vegetation but do notobviously affect the reflectivity of water and dry soil. The most bands show that thereflectivity of the marsh’s types has been directly affected by wind speed andinversely by relative humidity.